Kierunki kształtowania relacji z klientami na przykładzie administracji podatkowej - Kalisiak-Mędelska, Magdalena (Building Customers' Relations - the Case of Tax Authorities, 2007)
Presently tasks of public administration are regulated by the law. However, it fulfill much wider catalogue of tasks, ft is obliged not only to provide public services but also to find the best way to do it. It is the consequence of citizens' expectations who want services which meet their needs and preferences. Administration is challenged to change its structure into modern and more effective and, what is the most important, into customer oriented. This article focuses on some changes which take place in Polish tax administration. The author describes important for the administration relations with taxpayers. She gives many examples of solutions applied by one unit of tax administration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 634-643